2010
DOI: 10.1002/pssc.201000227
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of polysilicon nanowires for device applications

Abstract: All‐organic photopatterned 4×4 one‐diode–one‐resistor (1D–1R) cell arrays are presented by Tae‐Wook Kim, Alex Jen, and co‐workers . The all‐organic type photopatterned 4×4 1D–1R cell array architecture not only improves reading accessibility, but also prevents cross‐talk with neighboring cells. Each 1D–1R cell in the array architecture shows excellent switching performance, which suggests that such memory devices can be used for future advanced nonvolatile memory applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…It confirms the lower interface quality at the bottom part of SiNWs compared to its upper part. In other words, the upper part of the nanowires is better quality than lower part, which was supposed in a previous study [35]. In addition, these results confirm that in the GAA configuration, channel could be formed preferably in the upper region of SiNWs and leading to similar electrical characteristics for TGT configuration.…”
Section: Accepted M Manuscriptsupporting
confidence: 85%
“…It confirms the lower interface quality at the bottom part of SiNWs compared to its upper part. In other words, the upper part of the nanowires is better quality than lower part, which was supposed in a previous study [35]. In addition, these results confirm that in the GAA configuration, channel could be formed preferably in the upper region of SiNWs and leading to similar electrical characteristics for TGT configuration.…”
Section: Accepted M Manuscriptsupporting
confidence: 85%
“…As shown in figures 2 (a) and (b), doping effect is different with phophorus or boron doping species. A first partial study, previously reported by our group [23] on the N-type in-situ doping control on high curvature radius (100nm) polycrystalline silicon NWs, showed that the resistivity increasing the doping level from about 1× 10 18 cm -3 results in an abrupt resistivity drop of about 6 orders of magnitude for only a factor of 10 further increase in doping concentration. Beyond that range resistivity decreases to reach the same value as for crystalline silicon.…”
Section: Resultsmentioning
confidence: 88%
“…Top-down approach usually uses RIE etching, which are costly to avoid any unsuspected etching profile [3], [5], [6]. However, in bottom-up approach, atoms assemble one at a time in predetermined order or metal catalytic growth [3]. It also provides atoms or molecules in the structure to be held covalently which are strong and reliable.…”
Section: Introductionmentioning
confidence: 99%
“…The top-down method starts with a large structure followed by patterning and etching the smaller features, hence producing a nanostructure [5]. Top-down approach usually uses RIE etching, which are costly to avoid any unsuspected etching profile [3], [5], [6]. However, in bottom-up approach, atoms assemble one at a time in predetermined order or metal catalytic growth [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation